Anatomical Study of the Axillary Nerve: Description of a Surgical Blind Zone. Issue 2 (August 2016) - Maldonado, Andrés A.; Howe, Benjamin M.; Lawton, Rich; Bishop, Allen T.; Shin, Alexander Y.; Spinner, Robert J.
Abstract : Background: The aim of this study was to quantify the length of the axillary nerve that is able to be dissected through a standard anterior (deltopectoral) and posterior approach. The authors hypothesize that a segment of the axillary nerve cannot be reached using both approaches simultaneously. Methods: Axillary nerves of five frozen cadavers were dissected using an anterior and posterior approach. A first surgical clip marked the most visible distal part of the nerve from the deltopectoral approach; a second surgical clip marked the most proximal part from the posterior approach. The two surgical clips were localized with a shoulder radiograph. The authors performed measurements of the different axillary nerve segments. Results: In all specimens, there were three zones of the axillary nerve: zone A (anterior), the nerve segment from the origin of the axillary nerve to the first surgical clip, located at the level of the triangle formed by the subscapularis muscle (medial), conjoined tendon (lateral), and axillary fat (inferior); zone B (blind), the nerve segment not reachable through both approaches, from the first to the second surgical clip; and zone C (circumflex), the nerve segment from the second surgical clip (located at the level of the quadrilateral space) to entry into the deltoid muscle. The mean length of the blind zone was 1.6 cm. This blind zone was found 1 to 2 cm from the glenohumeral joint. Conclusion: The authors have described a segment of the axillary nerve that cannot be evaluated through anterior and posterior combined approaches.